Address delivered at the opening of the Eighth Session of the Society - Pim, Jonathan (Dublin Statistical Society, 1855)
Before venturing to ask your attention to the few remarks, which as one of the vice-presidents, I am about to make on the opening of this the eighth session of the Dublin Statistical Society, I must first express my warm acknowledgments for the kindness which has placed me in this honorable position. I feel that I have no claim on account of any services rendered to the cause of science, however sincere have been my desires to assist in promoting the investigation of some of those social and economic questions which are so closely connected with the prosperity of the country. The changes which have taken place during the seven years which have elapsed since the formation of this Statistical Society have been many and various; and among the most important has been that alteration in public feeling which has disconnected political economy from party politics, and thus permitted U3 to continue our inquiries into the important truths of this science, without the restraints which prejudice and party considerations had so long imposed upon us.
Read November 20th, 1854
Keywords: 314.15